Folkloristik 2003 : fire folkloristiske essays : pamflet - Hemmersam, Flemming (Hemmersam, 2003)
Summary: Folkloristics 2003 : four folkloristics essays.
Keywords: folkloristiikka; kansatiede; teoriat; folkloristik; etnologi; teorier